2019
DOI: 10.3390/polym11071086
|View full text |Cite
|
Sign up to set email alerts
|

Emission Properties of Diblock Copolymers Composed of Poly(ethylene glycol) and Dense 1,2,3-Triazole Blocks

Abstract: This article describes a new block copolymer (EGm-b-APn, where m and n denote the degrees of polymerization) of poly(ethylene glycol) (PEG) and poly(1,4-(1-H-1,2,3-triazolylene)methylene) prepared by copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) polymerization of 3-azido-1-propyne (AP) in the presence of PEG carrying a propargyl moiety. The EGm-b-APn samples are well soluble in polar organic solvents. Unexpectedly, we observed that solutions of EGm-b-APn in N,N-dimethylformamide emitted fluorescence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…These data indicate that the t-butyl ester group markedly improves the solubility of polymers of AP derivatives, resulting in the formation of higher molecular weight polymers. Our previous work on diblock copolymers of PEG and AP blocks demonstrated that the dense 1,2,3-triazole block emitted weak fluorescence in the molecularly dispersed state [35]. Thus, the photophysical behavior of solutions of the poly(tBuAH) samples in DMF was preliminarily examined by steady-state fluorescence spectroscopy because fluorescent polymers may be applicable to some fields, e.g., energy conversion and sensing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that the t-butyl ester group markedly improves the solubility of polymers of AP derivatives, resulting in the formation of higher molecular weight polymers. Our previous work on diblock copolymers of PEG and AP blocks demonstrated that the dense 1,2,3-triazole block emitted weak fluorescence in the molecularly dispersed state [35]. Thus, the photophysical behavior of solutions of the poly(tBuAH) samples in DMF was preliminarily examined by steady-state fluorescence spectroscopy because fluorescent polymers may be applicable to some fields, e.g., energy conversion and sensing.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the poor solubility, it was not possible to obtain high-molecular-weight polymers from the AP derivatives by CuAAC polymerization. However, it was possible to obtain dense 1,2,3-triazole oligomers or polymers soluble in common solvents by quaternization of the AP oligomer with methyl iodide [ 34 ] or by connecting to poly(ethylene glycol) (PEG) blocks, i.e., the formation of block copolymers [ 35 , 36 ]. The block copolymers of PEG and dense 1,2,3-triazole blocks form aggregates in water, e.g., spherical micelles and vesicles, depending on the ratio of block lengths, and undergo phase separation at higher temperatures because of cooperative dehydration of the PEG block [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…CuAAC has been also utilized for synthesis of polymers possessing 1,2,3-triazole units [ 23 , 24 , 25 , 26 ]. We have been working on synthesis of polymers with the backbone composed of dense 1,2,3-triazole units by CuAAC polymerization of 3-azido-1-propyne (AP) and its derivatives [ 27 , 28 , 29 , 30 , 31 ]. Unfortunately, AP polymer was insoluble in all the solvents examined presumably because of strong dipole–dipole interaction of dense 1,2,3-triazole units.…”
Section: Introductionmentioning
confidence: 99%
“…These oligomers were insoluble in all the common solvents examined because of the cooperative dipole–dipole interaction of dense 1,2,3‐triazole units. Recently, we have synthesized a new diblock copolymers of poly(ethylene glycol) (PEG) and dense 1,2,3‐triazole blocks, poly(ethylene glycol)‐ b ‐poly(3‐azido‐1‐propyne) (EG m ‐ b ‐AP n ), where m and n denote the degrees of polymerization (DP) of PEG and dense 1,2,3‐triazole blocks, respectively, to study the functions of dense 1,2,3‐triazole units in solution . In this study, we investigate the association behavior of EG m ‐ b ‐AP n and poly(ethylene glycol)‐ b ‐poly(3‐azido‐1‐butyne) (EG m ‐ b ‐AB n ) using the strong dipole–dipole interaction of dense 1,2,3‐triazole blocks.…”
Section: Introductionmentioning
confidence: 99%